Legal Aspects and Legal Implications of Auctioning Goods Through Social Media Platforms - Soni Barumuli; Ismail Ismail; Dewi Iryani (Devotion : Journal of Research and Community Service, 2026)
The purpose of this study is to determine and analyze the application of the death penalty to perpetrators of narcotics crimes according to Indonesian positive law. In discussing this research, the author uses the theory of legal certainty and the theory of punishment. This research is a normative legal study using library methods that focus on reading and analyzing primary and secondary legal materials. The results indicate that the death penalty remains in Indonesian positive law, as seen in various provisions in the Criminal Code and other laws and regulations. With the enactment of Law No. 1 of 2023 concerning the Criminal Code, the death penalty is no longer a principal punishment but a special punishment threatened using an alternative system. This means the execution can be postponed with a 10-year probationary period; if the convict shows improvement, it can be commuted to life imprisonment or 20 years' imprisonment, but if no behavioral improvement is shown, the death penalty can be carried out. The Criminal Code and Law No. 35 of 2009 explicitly impose the death penalty for serious drug offenders. This penalty is the harshest sanction for drug offenders because it deprives them of their right to life; however, it is commensurate with the consequences of their actions.